2008
DOI: 10.1038/modpathol.2008.70
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of non-sulfated chondroitin correlates with adverse clinicopathological parameters in prostate cancer

Abstract: Chondroitin sulfate is a structurally diverse glycosaminoglycan, which contains a variable degree of sulfation that helps to determine its biological function. It is involved in the regulation of cellular activity and has been implicated in carcinogenesis. To determine if the non-sulfated chondroitin backbone has a functional role in prostate cancer, we analyzed its expression by immunohistochemistry using the 1B5 monoclonal antibody and a set of tissue microarrays constructed with 227 prostate specimen cores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…In several studies, the level of HA was found to be associated with the degree of severity and spread of the disease through the body (Kramer et al, 2010;Paiva et al, 2005;Pham et al, 1997;Vizoso et al, 2004). Other studies found a link between poor prognosis in prostate cancer and undersulfation in CS (Teng et al, 2008) or elevated levels of CS (Ricciardelli et al, 1997(Ricciardelli et al, , 1999. Undersulfation in CS has also been linked to higher levels of prostate cancer relapse (Sakko et al, 2008).…”
mentioning
confidence: 99%
“…In several studies, the level of HA was found to be associated with the degree of severity and spread of the disease through the body (Kramer et al, 2010;Paiva et al, 2005;Pham et al, 1997;Vizoso et al, 2004). Other studies found a link between poor prognosis in prostate cancer and undersulfation in CS (Teng et al, 2008) or elevated levels of CS (Ricciardelli et al, 1997(Ricciardelli et al, , 1999. Undersulfation in CS has also been linked to higher levels of prostate cancer relapse (Sakko et al, 2008).…”
mentioning
confidence: 99%
“…Chondroitin sulfate as part of the tumor microenvironment accumulates in the stromal compartment of many solid tumors, including breast tumors (Olsen et al, 1988;Kovalszky et al, 1990;Alini and Losa, 1991;Ricciardelli et al, 1997Ricciardelli et al, , 1999Ricciardelli et al, , 2009Vijayagopal et al, 1998;Suwiwat et al, 2004;Pothacharoen et al, 2006;Sakko et al, 2008;Teng et al, 2008;Kalathas et al, 2009), the functional relevance of which had not been analyzed so far. Here, we utilized intra-tumor injections of ChABC in an orthotopic mouse model to demonstrate that enzymatic elimination of endogenous breast cancer-associated chondroitin sulfate leads to an increased metastatic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have also begun to elucidate potential roles for chondroitin sulfates and CSPGs in tumor biology. Strikingly increased levels of chondroitin sulfates and CSPGs have been observed in the microenvironment of a number of human solid tumors, including melanoma, ovarian adenocarcinomas, hepatocarcinoma, prostate tumors, colon adenocarcinoma, and breast cancer (Olsen et al, 1988;Kovalszky et al, 1990;Alini and Losa, 1991;Ricciardelli et al, 1997Ricciardelli et al, , 1999Ricciardelli et al, , 2009Vijayagopal et al, 1998;Suwiwat et al, 2004;Pothacharoen et al, 2006;Sakko et al, 2008;Teng et al, 2008;Kalathas et al, 2009). The functional significance of this observation for cancer progression is unknown, but increased deposition of chondroitin sulfates within malignant tissues raises the possibility of a cancer therapy targeted towards tumor-associated chondroitin sulfates.…”
Section: Introductionmentioning
confidence: 99%
“…21,24,25 Moreover, this tightly controlled chondroitin sulfation balance has been shown to be disturbed in human disease and malignancies. [26][27][28][29][30][31] Carbohydrate sulfotransferase 11/Chondroitin-4-sulfotransferase-1 (CHST11/C4ST-1; subsequently named C4ST-1) catalyzes the transfer of sulfate to the C-4 position of CS disaccharides, thus creating chondroitin-4-sulfate (C4S) as one of its products. 21 We have recently generated a loss-of-function mutation in C4ST-1 and demonstrated severely decreased C4S levels and severe cartilage defects in homozygous mutant mouse embryos.…”
Section: Introductionmentioning
confidence: 99%